REINTERPRETASI SUNNAH (Studi Pemikiran Muhammad Syahrur terhadap Sunnah) - Azhari Andi; Luqman Hakim; Mutawakkil Hibatullah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Discussion on Sunnah were never ended, like an never drying sea. It has been discussed since the Prophet era up to date, both by moslem scholars as well non-moslem (outsiders). One of the evidences is the emergence of Muslim scholars with their comprehensive and enlightening works such as Muhammad Shahrur. One controversial contemporary Muslim scholars, Shahrur encourage muslims in sueding and opposing concept against sunnah which has been agreed by the majority of ‘Ulama. In order to unfold his arguable idea, this article will discuss Shahrur’s thought on sunnah using descriptive-analytic method.